Plasma Lipids and Apolipoproteins in Young Female Swimmers and Gymnasts - Zonderland, M. L.; Erich, W. B. M.; Bernink, M. J. E.; Peltenburg, A. L.; Wilms, P.; Havekes, L. (Biomechanics and Medicine in Swimming, 1983)
Regular physical activity affects the lipid metabolism and lipid profile and is also associated with decreased mass of body fat. Trained subjects have higher high density lipoprotein-cholesterol (HDL-C) and often lower low density lipoprotein-cholesterol (LDL-C) and triglyceride (TG) levels than sedentary persons (Wood and Haskell, 1979). Fat mass also seems to affect lipid metabolism. Obese persons often have elevated serum cholesterol and TG levels compared to leaner subjects. In obese groups, the fat mass correlates with the serum lipids, especially with TG, but in nonobese groups these correlations are very low (Ylitalo, 1981). Therefore, the effect of training on lipid metabolism and lipid profile seems to be mainly due to activity itself with a very small part due to the decrease in body fat mass. These observations were made on adults, but there were indications that they are true for children, too (Gilliam and Burke, 1979; Laskarzewski et al., 1980). Erich (1980) reported that female gymnasts were leaner than control females of the same age. Female swimmers were found to have the same amount of body fat as control females (Astrand et al., 1963). Therefore, the lipid profiles and apolipoproteins in a group of female swimmers and gymnasts were investigated and it was proposed that differences in lipid profile and apolipoprotein levels would not be related to differences in body composition. The levels of total cholesterol (TC), HDL-C, free cholesterol (FC), TG, and total Iipids (TL), and the concentrations of the apolipoproteins A-I, A-II, and B (apo A-I, apo A-II, apo B) were measured. LDL-C was calculated and the following ratios were computed: HDL-C/TC, HDL-C/LDL-C, HDL-C/apo A-I, LDL-C/apo B, and apo A-I/apo B.